PENGARUH EKSISTENSIALISME TERHADAP PEMAHAMAN KEHIDUPAN REMAJA DI ERA DIGITAL - Nadya Rianda Qadri; Lulu Kamilah Ramadhanti; Muhammad Kemal Pahlevi; Lakeysha Larina Nurseptiani; Nadhifa Zahra Rafeyfa; Bintang Hafizh Setiawan; Gadiz Arifia Ayu; Dian Bagaskara; Fauzan Subiakto; Lutfi Hardiyanto (Prodi Sosiologi FISIP UPR, 2025)
The development of technology and social media presents new concepts and values that affect the life patterns of adolescents. This study aims to determine the influence of the concept of existentialism on the life patterns of adolescents who live in the midst of a digital era characterized by technological advances and social media. This research uses a quantitative method with data collection through a survey conducted using Google Form (GForm) and analysis of relevant journals. The results of this study show that the influence of existentialism on the pattern of life shows that there are mixed results regarding the impact of existentialism on the pattern of life of adolescents. This research provides a conclusion that existentialism has a major influence on the way teenagers understand and live life in the digital era. Dependence on gadgets and social media affects the way teenagers interpret their existence, freedom, and responsibility as individuals.